Experience conditioning in commuter modal choice modelling – Does it make a difference?. (November 2016) - Hensher, David A.; Ho, Chinh Q.
Highlights: An innovative way of exploring the role of overt experience in mode choice. Developing a way to predict overt experience to include in future mode choice. Key model outputs are derived and compared with those of traditional model. Abstract: This paper investigates the impact of decision maker's experience on model elasticities and predicted market share, using data collected in Sydney on commuter mode choice. Usage frequency is used as a proxy for experience and two separate mode choice models are estimated – one with experience conditioning choice and one without. Key model outputs are compared and we find that differences in the value of travel time savings and model elasticities are very marked. This suggests that ignoring experience that one has with each alternative in their choice set may be a candidate source of error in travel demand forecasts. We develop a method to obtain the level of experience for use in application of choice models to increase their prediction power.